Benzodithiophene‐Fused Perylene Bisimides as Electron Acceptors for Non‐Fullerene Organic Solar Cells with High Open‐Circuit Voltage. Issue 20 (22nd May 2019) - Tian, Zhongrong; Guo, Yiting; Li, Junyu; Li, Cheng; Li, Weiwei
Abstract: Tandem‐junction organic solar cells require solar cells with visible light photo‐response as front cells, in which an open‐circuit voltage ( V oc ) above 1.0 V is highly demanded. In this work, we are able to develop electron acceptors to fabricate non‐fullerene organic solar cells (NFOSCs) with a very high V oc of 1.14 V. This was realized by designing perylene bisimide (PBI)‐based conjugated materials fused with benzodithiophene, in which Cl and S atom were introduced into the molecules in order to lower the frontier energy levels. The fused structures can reduce the aggregation of PBI unit and meanwhile maintain a good charge transport property. The new electron acceptors were applied into NFOSCs by using Cl and S substituted conjugated polymers as electron donor, in which an initial power conversion efficiency of 6.63 % and a high V oc of 1.14 V could be obtained. The results demonstrate that the molecular design by incorporating Cl and S atom into electron acceptors has great potential to realize high performance NFOSCs. Abstract : Electron acceptors are developed to fabricate non‐fullerene organic solar cells with a very high V oc of 1.14 V. This is realized by designing perylene bisimide based conjugated materials fused with benzodithiophene, in which Cl and S atoms are introduced into the molecules to lower the frontier energy levels.